Educational Data Mining to support Distance Learning students with difficulties in the Portuguese Grammar - Soares, Fabiana M.; Machado, Crystiano J. R.; Diniz, Diógenes; Maciel, Alexandre M. A.; Rodrigues, Rodrigo L. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2016: Anais do XXVII Simpósio Brasileiro de Informática na Educação, 2016)
This work proposes the integration of a grammar checker and some EDM techniques in order to cluster students in a LMS according to their grammar difficulties in the Brazilian Portuguese Grammar. It used discussion forums’ posts and the results showed that it is possible to identify students’ main grammar difficulties and also to group them according to some specific ones.